COVID-19 vaccination literacy, attitude and hesitation towards vaccination and vaccination status of pregnant women - Kılıçlı, Ayşegül; Akbulut, Şahide (My University, 2023)
The study aims to determine COVID-19 vaccine literacy, attitude and hesitation towards the vaccine, and vaccination status of pregnant women in a rural region. This is a cross-sectional study. It was carried out between June 7 – 7 August 2022. 209 pregnant women were included in the study. The mean score of pregnant women was found to be COVID-19 vaccine literacy 2.5±0.4, attitude 3.1±0.8, and hesitation 7.7±6.6. It was found that 12.4% of the pregnant women had COVID-19 disease in their current pregnancy, and 7.2% of them had COVID-19 disease in the first trimester. It was determined that 34.4% of the pregnancy had a single dose, 30.2% had two doses, and most of them were BioNTech vaccines. Vaccine literacy was determined to be higher in pregnant women who are working, have social security, have a higher income than their expenses and have a master's degree. Those who are married, have social security, and have a female baby have a positive attitude for vaccines. There was a positive significant relationship between COVID-19 vaccine literacy and attitude, and a negative significant relationship between COVID-19 vaccine literacy and hesitancy. It was discovered that COVID-19 vaccine literacy is moderate, vaccination rates are low, and vaccination literacy influences vaccination attitudes and hesitation.